Potential role of (18)F-2-fluoro-2-deoxy-glucose positron emission tomography/computed tomography imaging in patients presenting with generalized lymphadenopathy - Karunanithi, Sellam (Indian J Nucl Med, 2015)
Generalized lymphadenopathy is a common and often vexing clinical problem caused by various inflammatory, infective and malignant diseases. We aimed to review briefly and highlight the potential role of (18)F-2-fluoro-2-deoxy-glucose ((18)F-FDG) positron emission tomography/computed tomography (PET/CT) in such patients. (18)F-FDG PET/CT can play an important role in the management of generalized lymphadenopathy. It can help in making an etiological diagnosis; can detect extranodal sites of involvement and employed for monitoring response to therapy.